Feeding grounds for wildfowl - The provision of feeding grounds for wildfowl on agricultural land - Matthews, G V T (Wildfowl, 1957)
In the European wildfowl system, the British Isles are predominantly wintering grounds–for birds that breed in Iceland, Greenland, Scandinavia and Russia. Apart from a substantial population of Mallard, breeding ducks and geese are rather sparsely scattered or absent. It is doubtful whether attempts to increase the breeding of wildfowl in Britain other than Mallard could produce a worth-while effect on the European population. The system of wildfowl refuges which is being built up will therefore be concerned primarily, though not exclusively, with providing protection for wintering flocks while they roost and feed.